Can Promoting Use of Public Transportation Improve People's Health? - Relationship Analysis Among Health, Lifestyle and Transportation Habit Considering Gender Difference. (June 2018) - Kanda, Yusuke; Akagi, Daisuke; Taniguchi, Ayako
Abstract : It is often said that lifestyle is quite important for better health. Especially, improvement of physical activity level brings better effects on individual's health condition. Non-car transportation use such as walk, bicycle, and public transportation provides more opportunity to exercise. It means that promoting of non-car use may improve people's health. However, in the context of limited availability of statistical data for analysis, its possibility has not been discussed deeply and clearly in Japan. This research aims to identify relationship focusing on people's transportation habit and health, especially considering difference between male and female. In particular, with health index data such as life expectancy, medical cost per capita, morbidity and mortality of lifestyle-related disease, and lifestyle index such as vegetable, alcohol intake and smoking habit, and transportation habit index such as share of car / public transportation / bicycle mode on commuting and average daily walk steps. The authors analyze these relationship with these data aggregated in almost all Japanese prefectures (regions) unit by correlation and regression analysis, As a result, significant relationship is identified between some health indexes and lifestyle indexes, in particular, life expectancy, medical cost per capita and morbidity of several disease in health index, and vegetable and alcohol intake in lifestyle index, as similar as generally discussed. However, relationship with transportation habit is also significantly identified. In particular, where "modal share of public transportation on commuting" is higher, morbidity of diabetes, high-blood pressure, cardiac, ischemia and mental disease, and medical cost per capita significantly tend to lower. The results indicate that not only improvement of "lifestyle with food, smoke and drink" as generally recognized, but also increase of "use of public transportation / bicycle / walk" or decrease of "use of car" may contribute to decrease a risk of suffering lifestyle-related disease, and to reduce medical expense. Promoting non-car use and public transportation use, which make more opportunity of physical activity in daily life can improve individual's health, and also improve social expense on medical cost. Based on these results, policy development cooperation of transportation and health is highly expected.